Optimal Control and Stability Analysis of Malaria Disease: A Model Based Approach - Mandal, Manotosh; Jana, Soovoojeet; Pahari, U. K.; Kar, T. K. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper we have proposed a three dimensional mathematical model on malaria disease by considering two distinct classes namely susceptible and infected human population and infected mosquito population. Basic reproductive number of the system has been obtained and its relation regarding the behavior of the system has been established. Two control parameters, namely treatment control on infected human population and insecticide control on mosquito populations are applied in the present system. We formulate and solve the optimal control problem considering treatment and insecticide as the control variables. All the theoretical results are verified by some computer simulation works.